Superoxide dismutase: Challenges, opportunities, and promises for clinical translation - Rasheed, Zafar (International Journal of Health Sciences, 2024)
Superoxide dismutase (SOD) is a crucial enzyme in the antioxidant defense system, playing a pivotal role in scavenging superoxide radicals and maintaining cellular redox balance. Its therapeutic potential has garnered significant attention in various fields, including medicine, biotechnology, and cosmetology. However, despite promising preclinical evidence, the clinical translation of SOD-based therapies faces numerous challenges, including issues related to formulation, delivery, pharmacokinetics, and efficacy. This editorial article critically examines the current status of SOD-based therapeutics, identifies key challenges hindering their clinical translation, and explores potential strategies to overcome these obstacles. By addressing these challenges and capitalizing on emerging opportunities and promises, the full therapeutic potential of SOD may cover the ways for the development of effective antioxidant therapies for a wide range of human diseases.